Research Trends in Creative Arts of Career Counseling: A Bibliometric Analysis - Afriyati, Vira; Suherman, Uman; Adiwinata, Anne Hafina; Aden, Edris bin (Universitas Negeri Padang, 2024)
The objective of this study is to perform a bibliometric analysis of the current research trends related to the integration of creative arts in career counselling activities. This analysis will be carried out using the VOSviewer analytic tool and data obtained from the Scopus database. We have compiled the findings of a study conducted between 1972 and 2024, which consists of a total of 26 papers. Bibliometric approaches gather and analyse data from many scientific articles, journals, and conferences that are pertinent to this subject. The data reveals a substantial increase in research on creative arts in the field of career counselling in recent years. Key study areas encompass the utilisation of art as a means to comprehend personal interests and abilities, as well as the incorporation of art in the process of selecting professional choices. The findings of this analysis offer significant perspectives for career counselling professionals, researchers, and other interested parties in comprehending the present patterns in the utilisation of creative arts in career counselling endeavours. This study significantly enhances our comprehension of the arts' function in career guidance and can establish a basis for future research in this field.